PENGARUH LAMA HIDROLISIS H2SO4 DAN KONSENTRASI MOLASE TERHADAP FERMENTASI TEPUNG ONGGOK UNTUK MENGHASILKAN BIOETANOL - Septaristya Umeksi (FP AGRO 16 UMY 032, 2016)
The research aimed to study H2SO4 during hydrolysis and the role of molasses in the yield of fermentation. Experiment was designed in CRD (Completely Randomized Design)with six treatments : (1) 3 hours of H2SO4 hydrolisis adding with 10% of molasses, (2) 4 hours of H2SO4 hydrolisis adding with 10% of mollases, (3) 5 hours of H2SO4 hydrolisis adding with 10% of mollases, (4) 3 hours H2SO4 hydrolisis adding with 15% of mollases, (5) 4 hours of H2SO4 hydrolisis adding with 15% of mollases, and (6) 5 hours H2SO4 hydrolisis adding with 15% of mollases. Result showed that the longer of H2SO4 hydrolisis and the higher of mollases concentration produced higher percentage of sugar. Hydrolysis in 5 hours and mollases concentration of 15% gave the best result on sugar production. However the highest concentration of ethanol was obtained in 3 hours hydrolysis with mollasees concentration of 15%.